Women writers and detectives in nineteenth-century crime fiction the mothers of the mystery genre - Sussex, Lucy 1957- (Crime files series, 2010)
"This book is a study of the "mothers" of the mystery genre. Traditionally the invention of crime writing has been ascribed to Poe, Wilkie Collins and Conan Doyle, but they had formidable women rivals, whose work has been until recently largely forgotten. The purpose of this book is to "cherchez les femmes," in a project of rediscovery"--Provided by publisher